Modelagem de vulnerabilidade de sistemas ambientais no municípo de Guadalupe/PI - Costa, Tiago Barreto de Andrade (2008)
In the Guadalupe city, with the arrival of the Boa Esperança Hydroelectric, the landscape of the municipal district lived important transformations. Those transformations continue growing today, now together with new vectors of territorial ordering, especially the agricultural industry. In front of the context of stability-instability of the environmental systems, it original of its natural vulnerability to the instability and of the transformations in the territorial dynamics of Guadalupe, the present research it analyzed and it mapped that municipal territory with relationship to the degrees of vulnerability of the environmental systems. Therefore, working a leaning methodology in a systemic perspective of the landscape and in the geoprocessing technique, the dissertation showed with thematic mapping, the most vulnerable and less vulnerable parts of the municipal district of Guadalupe, looking for a strategic vision of the problem.